(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
This article considers the change in the insurance market for 2017. The comparative characteristics of the types of insurance. The modern insurance market is characterized by a slight increase, which is close to its rate of inflation. In the future, also, the smooth growth rate of the analyzed market is predicted with insignificant recessions related to business activity in the market.